(untitled) (Journal of Hama University, 2026)
The research aimed to identify the problems facing teachers of the first stage of primary education in Tartous city schools while performing their occupation from their perspective using the descriptive method. The research sample consisted of(266) male and female teachers from the teachers of the first stage of primary education in Tartous city government schools for the academic year 2023-2024 AD, based on a questionnaire prepared by the researcher. After verifying its validity and credibility, the research reached the following conclusions: There are problems facing teachers of the first stage of primary education in Tartous city schools while performing their occupation from their perspective . The problems relating to parents came in first place with an average of(3.0387), and the problteachersems related to school administration came in second place with an average of(2.9323), and the problems related to students came in last place with an average Of (2.9029).